Prevalence of overweight in adolescents from a Southern Brazilian city according to different anthropometric indexes - Augusto Gerhart Folmann; Vaneza Lira Waldow Wolf; Everton Paulo Roman; Gil Guerra-Júnior (Sociedade de Pediatria de São Paulo, 2020)
ABSTRACT Objective: To identify the prevalence of overweight in adolescents according to different classification criteria for obesity and somatic maturation stages. Methods: Cross-sectional study in 10 schools in a city from Southern Brazil, with 1715 adolescents. Height, weight, waist circumference, and neck circumference (NC) data were collected. Body Mass Index was classified according to World Health Organization (WHO) and Centers for Disease Control and Prevention criteria, and the waist-to-height ratio (WHtR) was classified according to Brazilian and European cut-off points. Somatic maturation was obtained through the Peak Height Velocity. The prevalence data were compared between sex and stages of somatic maturation; the concordance between different criteria was verified. Results: The prevalence of overweight was high in both sexes; WHO criteria showed that 34.5% of boys and 29.3% of girls were overweight. For the WHtR, the prevalence was 28.4% in boys and 23.7% in girls. NC classified 13.8% of boys and 15.8% of girls as being overweight. The prevalence of overweight was higher in adolescents before complete somatic maturation. Conclusions: The prevalence of overweight was high among adolescents. The boys presented higher frequency of overweight, except if NC was used to classify them. Adolescents before somatic maturation had a higher prevalence of overweight. NC showed a lower ability to track obese adolescents.